KanWork COVID-19 Vaccine Initiative - Mazanah Muhamad; Nor Aida Maskor; Asmah Ismail; Nik Hasnaa Nik Mahmood (Adult Education Research Conference, 2023)
COVID-19 triggered the need for vaccination. A mixed method inquiry revealed that KanWork Cancer Society’s vaccination initiative was successful in educating members to make informed decision to vaccinate.
Keywords: Vaccine; Covid-19; Cancer survivor; Informed decision; Adult Education